Economic Growth in Indonesia: The Influence of Fiscal Decentralization, Investment, Labor, and Human Development Index - Maulana, Harist; Syahnur, Sofyan; Abrar, Muhammad (Graha Primera Saintifika, 2025)
Economic growth is the main indicator of the success of a region's development. This study aims to analyze the effect of fiscal decentralization, investment, labor, and the Human Development Index (HDI) on economic growth in Indonesia. Fiscal decentralization is measured through the General Allocation Fund (DAU), Revenue Sharing Fund (DBH), and Special Allocation Fund (DAK), while investment is represented by Domestic Direct Investment (PMDN) and Foreign Direct Investment (PMA). The labor factor is measured based on the number of workers employed, while the HDI is used as an indicator of human resource quality. This study uses a quantitative approach, employing panel data regression with the Ordinary Least Squares method. Data were collected from 34 provinces in Indonesia from 2014 to 2023. The results of the study show that DAU, DBH, and DAK have a positive and significant effect on economic growth, indicating that fiscal transfers from the central government to the regions can encourage economic activity at the regional level. In addition, PMDN and PMA also have a significant positive impact on economic growth. However, labor does not show a significant effect on economic growth, indicating that the increase in the number of workers has not been accompanied by an increase in skills and work productivity. Meanwhile, the HDI has a positive and significant effect, confirming that improving the quality of education and health plays an important role in increasing labor productivity and economic growth. These findings emphasize the importance of optimizing fiscal policy, increasing the effectiveness of regional fund allocation, and workforce development and human development strategies to support sustainable economic growth in Indonesia.